EFFECT OF DIETARY REPLACEMENT OF FISH MEAL BY FISH SILAGE BASED MIXED PROTEIN SOURCE ON GROWTH PERFORMANCE SILVER BARB (PUNTIUS GONIONOTUS) FRY - LENKA, R.; SAHU, B.; CHOUDHURY, D.; DAS, S. S.; KUMAR, SHIVENDRA; DAS, N.; MOHANTA, K. N. (Journal of the Inland Fisheries Society of India, 2026)
The study evaluated the effect of dietary fish meal replacement with fish silage based mixed protein (FSMP) source on growth and survival of silver barb fry. For this purpose five isonitrogenous diets were formulated namely T0 (fish meal based control diet), T1 (25% fish meal replacement by FSMP), T2 (50% fish meal replacement by FSMP), T3 (75% fish meal replacement by FSMP) and T4 (100% fish meal replacement by FSMP). FSMP was prepared with one third each of fish silage, groundnut oil cake and soya bean meal on dry weight basis. 225numbers of silver barb fry of average weight (1.0±0.08 g) were randomly distributed in five treatments with triplicates following a completely randomized design and fed with different experimental diets for a period of 90 days. At the end of the experiment the weight gain percentage was significantly (P